Target specificity of neuropeptide Y-immunoreactive cranial parasympathetic neurons - Leblanc, GG (J Neurosci, 1988)
We recently showed that neuropeptide Y (NPY)-like immunoreactivity occurs in subpopulations of neurons in 3 cranial parasympathetic ganglia: the otic, sphenopalatine, and ciliary. The present work identifies the target tissues innervated by cranial parasympathetic NPY- immunoreactive neurons. Plexuses of NPY-immunoreactive fibers were observed in the parotid gland, the target of the otic ganglion, and in the intraorbital lacrimal gland and palate, targets of the sphenopalatine ganglion. NPY-immunoreactive fibers of apparent parasympathetic origin innervated glandular acini in all 3 structures and were also present around small blood vessels in the parotid and intraorbital lacrimal glands. These fibers were presumed to be parasympathetic because they were not affected by removal of the superior cervical ganglion and because their distribution was coextensive with that of vasoactive intestinal polypeptide (VIP) immunoreactivity, which we have previously shown to be colocalized with NPY in the cell bodies of otic and sphenopalatine ganglion neurons. In contrast, no NPY-immunoreactive fibers were observed in the iris or ciliary body of acutely sympathectomized rats, suggesting that NPY- immunoreactive neurons in the ciliary ganglion do not normally transport detectable levels of NPY to their terminals. The target specificities of cranial parasympathetic NPY-immunoreactive neurons are different from those of sympathetic NPY-immunoreactive neurons. Sympathetic NPY-immunoreactive fibers innervated the iris and ciliary body, and the blood vessels but not the parenchymal cells of all the glands examined. In contrast, parasympathetic NPY-immunoreactive fibers primarily innervated glandular acini. NPY-immunoreactive neurons in the sphenopalatine ganglion displayed an additional level of specificity in their projection pattern in that they innervated only a subset of the ganglion's array of target glands: they innervated the intraorbital lacrimal gland and the seromucous glands of the palate but not the exorbital lacrimal gland or the glands of the nasal mucosa. The finding that NPY immunoreactivity is present in the parasympathetic innervation of secretory acini in several craniofacial glands raises the possibility that NPY plays a role in the parasympathetic control of glandular secretion. The observed overlap in the distributions of NPY- and VIP-immunoreactive fibers in these glands further suggests that NPY may interact with VIP to stimulate secretion.